2002
DOI: 10.1088/0029-5515/42/2/310
|View full text |Cite
|
Sign up to set email alerts
|

Basic divertor operation in ITER-FEAT

Abstract: This paper summarises the modelling studies of steady-state divertor operation being performed for the ITER-FEAT design. Optimisation of the divertor geometry reveals the importance of the proper target shape for a reduction of the peak power loads. A high gas conductance between the divertor legs is also essential for maintaining acceptable conditions in the outer divertor which receives higher power loading than the inner. Impurity seeding, which would be necessary if tritium co-deposition concerns preclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 9 publications
4
66
0
Order By: Relevance
“…A number of modelling results on the performance of the ITER divertor have been obtained in last five years [511,516,253,29,517,20,513,512,515] as new experimental results have been obtained, further physical effects have been included and a design optimisation of ITER toward lower cost has been performed. The primary aim of the studies has been the identification of the major control parameters, the exploration of the operational window, the investigation of the effect of divertor geometry, and the development of integrated modelling of the whole plasma by coupling of the edge and core models at their interface.…”
Section: Modelling Resultsmentioning
confidence: 99%
“…A number of modelling results on the performance of the ITER divertor have been obtained in last five years [511,516,253,29,517,20,513,512,515] as new experimental results have been obtained, further physical effects have been included and a design optimisation of ITER toward lower cost has been performed. The primary aim of the studies has been the identification of the major control parameters, the exploration of the operational window, the investigation of the effect of divertor geometry, and the development of integrated modelling of the whole plasma by coupling of the edge and core models at their interface.…”
Section: Modelling Resultsmentioning
confidence: 99%
“…However, recent results have shown that the plasma fluxes on the wall can be higher than expected from this simple exponential decay, due to turbulent transport across the field lines [16]. Present modelling [11,17] …”
Section: Iii-1) Parameters Of the Plasma In Contact With Plasma Facinmentioning
confidence: 89%
“…This allows to access to the detached divertor regime [10], which is the reference for ITER divertor operation [11]. In the detached divertor regime, dissipation of the power conducted/convected by the plasma by the high densities due to intense hydrogen recycling, impurities radiation, and partial recombination of the impinging particle flux allows to keep peak power fluxes on the divertor targets under ~ 10 MWm -2 , while maintaining adequate central plasma purity [11]. The corresponding ITER plasma parameters along the divertor target estimated from modelling are shown in Fig.…”
Section: Iii-1) Parameters Of the Plasma In Contact With Plasma Facinmentioning
confidence: 99%
See 2 more Smart Citations